MULTILINGUALISM USED BY UMM BUDDIES FOR CONDUCTING INTERVIEW IN THE LEARNING EXPRESS PROGRAM AT UNIVERSITY OF MUHAMMADIYAH MALANG - Ambika Putri Perdani; Hartono Hartono (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2018)
This study was focused on the implementation of multilingualism used by UMM buddies along with the problems and the solutions. The purposes of this study were: (1) to describe the implementation of multilingualism used by UMM Buddies in conducting interview at the Learning Express Program, (2) to uncover the problems faced by UMM Buddies in using multilingualism in conducting interview at the Learning Express Program, and (3) to investigate the ways UMM Buddies solved the problems in using multilingualism when conducting interview at the Learning Express program. The researcher described the result through interpretative and narrative description. Therefore, qualitative research design suited this study. There were two techniques to collect the data. They were observation and interview in which observation checklist and interview guide were employed as the instruments. The research findings showed that, in conducting interview at the Learning Express program, UMM buddies occupied multilingualism. They spoke English, Javanese (Ngoko/Krama) and Bahasa Indonesia. UMM buddies who implemented the multilingualism during the interview section were UMM Buddies I, as the interviewer, UMM Buddies II, as the note taker, and UMM Buddies III as the interpreter during the interview session.There were some problems faced by UMM buddies, namely: difficulty in the language selection and the fallacy in language pronunciation. The strategies applied in solving the difficulties in the language selection were by means of body language, Google Translate, and simple vocabulary use to convey the real meaning. Besides, the cooperative synergy of each role also helped to solve this problem and saved the interview process. Moreover, in dealing with the problem of the fallacy in language pronunciation, UMM buddies tried to get acquitted and began to develop their multilingual abilities through the improvement of their speaking habit